Investigating the Diversity of Bacteria and Fungi in Rock Pigeon (Columba livia) Stool using Metagenomics in Sarawak, Malaysian Borneo. - Vaenessa, Noni @ Boni (Universiti Malaysia Sarawak, 2024)
Rock pigeon (Columba livia), are domesticated birds, commonly found in urban areas worldwide. Apart from being a nuisance, pigeons are associated with 110 pathogens, with most studies focused on the bacterial and fungal diversity due to its zoonotic potential. Previously, culture-dependent techniques in diversity studies were preferred, including bacterial and fungal studies of pigeon stool. However, the technique underestimates presence of unculturable bacteria and fungi, ultimately inaccurately reporting the actual diversity. To this day, only one study respectively has described on the bacterial and fungal diversity using culture-independent techniques worldwide. Additionally, any microbiome data on pigeon stool has not been reported in Malaysia previously. Thus, to fill this knowledge gap, this study aims to characterise the bacterial and fungal diversity and to identify potentially pathogenic bacteria and fungi in pigeon stool found in towns of Sarawak using high- throughput amplicon sequencing and to identify potentially pathogenic bacterial and fungal genera. Six samples consisting of fresh and dry stool samples were collected from four towns in Sarawak, and its microbial composition was identified through sequencing of the V3 – V4 16S rRNA and ITS2 rRNA regions. A total of 1381 and 481 bacterial and fungal amplicon sequence variants (ASVs), respectively, were identified in pigeon stool, with dry pigeon stool having higher bacterial and fungal ASVs than fresh pigeon stool. Firmicutes was the dominating bacterial pigeon stool contributed by the presence of probiotic bacteria such as Sporosarcina, Clostridium sensu stricto 1, Romboutsia, Lactobacillus and Anerosporobacter, reflecting the pigeon gut microbiome. Whereas, the dominance of Proteobacteria in dry pigeon stool was attributed to the presence of enteric bacteria such as Escherichia-Shigella and Enterococcus, which have been found to proliferate upon the excrement from the gastrointestinal tract. On the other hand, dominance of Ascomycota is contributed by the presence of Kazachstania and Neocucurbutaria. However, environmental fungal genera including Aspergillus, Trichosporon, Penicillium, Iodophanus, and Cephaliophora contributed to the dominance of Ascomycota in dry pigeon stool. Additionally, 18 bacterial and fungal genera, respectively, were flagged as potentially pathogenic. Of these, four and six bacterial and fungal genera, respectively, were not previously associated with pigeon stool. This study gives insight into the importance of utilising high-throughput amplicon sequencing for bacterial and fungal diversity characterisation, depicting the important role of fresh and dry pigeon stool in the environment. Additionally, the detection of additional pigeon-related potentially pathogenic pathogens in study shows that geographical location and immune status of the bird plays a role in the prevalence of microbes.